Logistyczna obsługa klienta w organizacjach sieciowych - Długosz, Jan (Customer Logistics Service in Network Organizations, 2005)
Logistic customer service plays a very significant role in the success of companies. However, it is not fully recognized. In particular this concerns the way in which quality of customer service is created in the whole process. The mechanism of such services is particularly insufficiently known in network organizations. Different types of networks create differentiated conditions in this field. Of particular importance may be the nature of relations between the networks' elements. This means that a network organization can provide a client with a better service than ordinary enterprises but it may also hinder the course of such a process.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 50-56